Alternative Techniques for Teaching Writing - Sihindun arumi (IAIN Salatiga, 2015)
Writing as one of language skill is often considered very difficult. It is due to the fact that writing needs to produce and organize ideas using appropriate vocabulary, language use, paragraph organization, and mechanism. It also needs to turn the ideas into a readable text and for foreign language learners, they should also transfer ideas from their native language into target language (foreign language). It raises any problems for them to create a good text. Moreover, the situation in the class does not always supportthem in which the techniques of the teacher in teaching writing is boring and monotonous, do not give enough attention to help students explore their writing skills. So that they attend the writing class only for procedural formality.Thus, it is considered important to elaborate various techniques to build nice classroom atmosphere as well as to improve students’ writing skills.